2021
DOI: 10.1101/2021.08.05.21261643
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 Outcomes Among Users of CD20 Inhibitors for Immune-Mediated Diseases: A Comparative Cohort Study

Abstract: Objective: Patients with immune-mediated diseases treated with CD20 inhibitors may have worse COVID-19 outcomes due to impaired humoral immunity, but differences versus the general population are unknown. Methods: We identified patients with immune-mediated diseases who received CD20 inhibitors within one year prior to the index date of PCR-confirmed COVID-19 between January 31, 2020, and January 31, 2021. Comparators with COVID-19 were matched up to 5:1 by age, sex, and PCR date. Hazard ratios (HRs) and 95% c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 33 publications
(36 reference statements)
1
16
1
Order By: Relevance
“…Third, patients receiving anti-CD20 therapy (aCD20), i.e., obinutuzumab or rituximab, are at increased risk for COVID-19 mortality, prolonged infection, protracted viral shedding, and decreased protection as a result of vaccination [61]. While increased mortality was not evident in all cohorts [36], other [35, 120], well-designed (albeit retrospective) studies showed increased mortality risk (HR 2.16, 95% CI [1.03–4.54]) [120]. Perhaps more importantly, aCD20 deeply impairs the immune response to COVID-19 vaccination.…”
Section: Resultsmentioning
confidence: 99%
“…Third, patients receiving anti-CD20 therapy (aCD20), i.e., obinutuzumab or rituximab, are at increased risk for COVID-19 mortality, prolonged infection, protracted viral shedding, and decreased protection as a result of vaccination [61]. While increased mortality was not evident in all cohorts [36], other [35, 120], well-designed (albeit retrospective) studies showed increased mortality risk (HR 2.16, 95% CI [1.03–4.54]) [120]. Perhaps more importantly, aCD20 deeply impairs the immune response to COVID-19 vaccination.…”
Section: Resultsmentioning
confidence: 99%
“…While patients with IMIDs on BCDTs have been recognized to be vulnerable to severe COVID-19 infections, 3,4,6,7 relatively scant data exist regarding their risks for and outcomes of breakthrough infections 2,18 . The current cohort of breakthrough patients consisted of nearly equal numbers of patients with rheumatic and neuro-inflammatory disease and most (91.9%) were either fully vaccinated or boosted, with only 6 (8.1%) with incomplete vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…While there is great heterogeneity in the capacity of specific immunosuppressive agents to limit the integrated immune response to both natural infection as well as vaccines, of particular concern is the class of B cell depleting therapies (BCDTs) widely used to treat an array of IMIDs. Before the introduction of vaccines, treatment of both rheumatic and neurologic IMIDs with such BCDTs was associated with more severe COVID-19 [3][4][5][6][7][8][9] . Furthermore, numerous studies have documented the capacity for BCDTs such as rituximab and ocrelizumab to profoundly impair humoral response to numerous vaccines including SARS-CoV-2 [10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…As the pandemic has progressed, a higher risk of incident COVID-19 infection or worse outcomes in certain immunocompromised subpopulations, such as those with rheumatoid arthritis (RA) [ 1 , 2 ] has been described. This is potentially related not only to their underlying disease but also due to the use of immunosuppressive medications used to treat RA [ 3 , 4 ]. Specifically, some studies have raised concerns regarding rituximab (RTX) exposure being associated with worse COVID-19 outcome [3] , [4] , [5] , [6] .…”
Section: Introductionmentioning
confidence: 99%
“…This is potentially related not only to their underlying disease but also due to the use of immunosuppressive medications used to treat RA [ 3 , 4 ]. Specifically, some studies have raised concerns regarding rituximab (RTX) exposure being associated with worse COVID-19 outcome [3] , [4] , [5] , [6] . For example, Sparks et al, using the data from the global rheumatology alliance (GRA) that contained physician-reported survey data, found that people with RA who were treated with RTX or JAK inhibitor had worse COVID-19 severity (defined as hospitalization/death) than those on tumor necrosis factor inhibitors (TNFi) [5] .…”
Section: Introductionmentioning
confidence: 99%